Penyuluhan Pengolahan Sampah Plastik Prinsip 4R Mendukung Program Kampung Bantar, Kota Jambi - Lailal Gusri; Harmes; Fernando M. Putra; M Nuklirullah; Dyah Kumalasari; Hadrah; Anggrika Riyanti; Evi Adriani; Akhmad Irwansyah; Yunan Surono (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Jambi City has a Bantar Village program that has a variety of innovative development programs. Garbage and waste require effective processing to support Bantar Village. Method 1) Collection, cleaning, painting and waste of paint can. 2) Application of the 4R principle as a solution to reduce plastic waste. The purpose of the service is in the form of counseling to provide education and skills in making trash cans from paint cans to residents in RT16, Payo Selincah Village, Jambi City. The results of the paint can trash can products can be used by residents as one of the supporters of the Bantar Village program. Residents have the knowledge and skills in efforts to reduce plastic waste that can generate economic value.